2012
DOI: 10.1097/ajp.0b013e31822bb35b
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Adaptation and Validation of the painDETECT Scale Into Spanish

Abstract: The culturally adapted version of the painDETECT presents good psychometric properties and shows to be a valid patient-reported outcome for measuring the presence of a neuropathic component in patients with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
69
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 25 publications
22
69
1
1
Order By: Relevance
“…However, the seven-item version resulted in a slightly higher reliability (Cronbach’s α =0.80) than the nine-item version (Cronbach’s α =0.76) and more consistent item-level discrimination. The reliability of the seven-item version is not only similar to that reported in the validation study (Cronbach’s α =0.83),15 but its higher value than the nine-item version is also in concordance with previous observations,27 suggesting that the two nonsensory items are not psychometrically compatible with the sensory items. While further confirmation for the greater reliability of the seven-item version is needed, it can nevertheless be recommended that the seven sensory items be used together; the two nonsensory items, on temporal and spatial characterization of the pain pattern, that are included in the nine-item version can be analyzed and interpreted separately.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, the seven-item version resulted in a slightly higher reliability (Cronbach’s α =0.80) than the nine-item version (Cronbach’s α =0.76) and more consistent item-level discrimination. The reliability of the seven-item version is not only similar to that reported in the validation study (Cronbach’s α =0.83),15 but its higher value than the nine-item version is also in concordance with previous observations,27 suggesting that the two nonsensory items are not psychometrically compatible with the sensory items. While further confirmation for the greater reliability of the seven-item version is needed, it can nevertheless be recommended that the seven sensory items be used together; the two nonsensory items, on temporal and spatial characterization of the pain pattern, that are included in the nine-item version can be analyzed and interpreted separately.…”
Section: Discussionsupporting
confidence: 85%
“…Although there is a need for characterizing and quantifying NeP concurrently with its identification in patients with various NeP conditions, to our knowledge, no other NeP instrument has yet been specifically validated for distinguishing between levels of average pain severity. These results therefore complement and extend studies that have suggested that NeP-screening instruments may help distinguish among sensory symptom profiles and pain-severity levels 16,17,2527…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Ofrece una representación visual del patrón del curso del dolor con el tiempo para apoyar la identificación correcta del tipo de dolor y hace uso de un mapa sensorial para evaluar la presencia de dolor irradiado (14).…”
Section: Discussionunclassified